Calcifying cystic odontogenic tumor- a unique developmental lesion arising in mandible - Vasudev, S; Singh, VP; Jhawar, R; Roy, DK (Health Renaissance, 2012)
Calcifying cystic odontogenic tumor (CCOT) is a unique developmental lesion arising from the odontogenic epithelial remnants present in the jaw bones. It is a very rare lesion having a distinctive histopathologic appearance characterized by the presence of ghost cells with considerable amount of histopathologic diversity. The case report describes a rare and unusually large presentation of CCOT in an 18 year old female. The patient presented with a large swelling in the mandibular’ anterior region. After clinical, radiographic investigations, an incisional biopsy was performed and a diagnosis of CCOT was made. The cyst was enucleated with complete removal of cystic lining. The patient has recovered well and has been kept under observation. DOI: http://dx.doi.org/10.3126/hren.v10i1.6012 HREN 2012; 10(1): 64-68